2021
DOI: 10.1111/famp.12726
|View full text |Cite
|
Sign up to set email alerts
|

Parent immigration stress predicts youth externalizing behavior trajectories among Latino families in an emerging immigrant context

Abstract: According to ecodevelopmental and social learning models, Latino immigrant parents experience considerable stress associated with the immigration process, and such immigration‐related stress is theorized to influence behavioral outcomes among their youth. Using a three‐year longitudinal design among 217 Latino immigrant families in western Oregon, we assessed whether parents’ (94% mothers, Mage = 36.2 years) experience of immigration‐related stress influenced the trajectory of their adolescents’ (43% female, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…For Latino immigrant families, family dysfunction often occurs due to parent–child value discrepancies, financial hardship, and family disagreements (Ayón et al, 2017; Cervantes et al, 1991). In emerging contexts, where the number of stressors that impact the family are considerable (Cobb et al, 2020, Cobb & Martínez, 2021), families are likely to experience higher levels of cultural stress that influence youth development. Longitudinal work showed that higher levels of stress in the family context predicted the development and course of depression among adolescent youth (Costello et al, 2008; Kelly et al, 2016), and research on Latino immigrant families has found that family cultural stress can exacerbate or maintain youth mental health and problem behaviors (e.g., Cervantes et al, 1991; Cobb & Martínez, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For Latino immigrant families, family dysfunction often occurs due to parent–child value discrepancies, financial hardship, and family disagreements (Ayón et al, 2017; Cervantes et al, 1991). In emerging contexts, where the number of stressors that impact the family are considerable (Cobb et al, 2020, Cobb & Martínez, 2021), families are likely to experience higher levels of cultural stress that influence youth development. Longitudinal work showed that higher levels of stress in the family context predicted the development and course of depression among adolescent youth (Costello et al, 2008; Kelly et al, 2016), and research on Latino immigrant families has found that family cultural stress can exacerbate or maintain youth mental health and problem behaviors (e.g., Cervantes et al, 1991; Cobb & Martínez, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In emerging contexts, where the number of stressors that impact the family are considerable (Cobb et al, 2020, Cobb & Martínez, 2021), families are likely to experience higher levels of cultural stress that influence youth development. Longitudinal work showed that higher levels of stress in the family context predicted the development and course of depression among adolescent youth (Costello et al, 2008; Kelly et al, 2016), and research on Latino immigrant families has found that family cultural stress can exacerbate or maintain youth mental health and problem behaviors (e.g., Cervantes et al, 1991; Cobb & Martínez, 2021). The heightened sensitivity to stress among adolescent females, coupled with residing in the high-stress environment of an emerging context, may explain why females in our sample were disparately impacted by parent depression and why family stress disrupted their downward trajectory of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations